Behavioral intervention effect of social norm feedback on reducing clinicians' antibiotic prescribing: a meta-analysis - Lin SHI; Ying-chao ZENG; Wei-bin LI (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo evaluate intervention effect of social norm feedback (SNF) on reducing antibiotic prescribing behavior of clinicians and to provide a reference for decreasing irrational use of antibiotics. MethodsLiteratures published relevant to intervention effect of SNF on doctors' antibiotic prescribing behavior were retrieved through searching publications up to October 31, 2021 from China Journal Full-Text Database, VIP Journal Full-Text Database, WanFang Database, PubMed Database, Web of Science Database, Scopus Database, and EMBASE Database; the searching was supplemented using literature retrospective method. Stata 16.0 statistical software was adopted to perform meta-analysis. ResultsTotally 9 English literatures with 19 528 pooled participants were included in the analysis. The results of meta-analysis showed that SNF intervention can reduce the number of clinicians' antibiotic prescriptions by 4% (rate difference, [RD] = - 0.04, 95% confidence interval [95% CI]: - 0.06 - - 0.03). Further subgroup analysis indicated that all SNF interventions being carried out through following approaches could significantly reduce antibiotic prescription rate of clinicians: with short interval (< 3 months) or long interval ( ≥ 3 months), targeted at doctors or medical institutions, disseminating intervening information by letters and emails/electronic pop-up windows, and adopting fuzzy ranking evaluation (all P < 0.001). Sensitivity analysis and publication bias test demonstrated that the literatures included in the analysis had less publication bias and the results were relatively stable. Conclusion SNF intervention could restrain clinicians' antibiotic prescribing behavior.